Specialized knowledge of Portuguese Language teachers PLTSK: direct transposition of the MTSK (Research, Society and Development, 2020)
Studies on the specialized knowledge of teachers have been carried out for years in several countries, with the result that some theoretical models have been developed for the different areas of teaching. The research on the theoretical models of Physics (PTSK) and Chemistry (CTSK) started with the direct transposition of the Mathematics Teachers Specialized Knowledge model - MTSK, performing the definition and description of the domains and subdomains capable of characterizing the specialized knowledge of teachers of the disciplines. The purpose of this article was to evaluate the proposal for the development of the Portuguese Language model named Portuguese Language Teacher's Specialized Knowledge (PLTSK) based on the direct transposition of the MTSK. To perform the PLTSK modeling, initially, the identification of evidence of specialized knowledge in scientific articles classified as Professional and Pedagogical Experience Repertorie (PaP-eRs), described by Loughran et al. as articles that illustrate for the researcher the elements that characterize the knowledge of teachers and allow aspects of pedagogy, content and context to be recognized. The methodological guidance will be of an analytical-interpretative nature, with qualitative research, which will make it possible to systematically determine the specialized knowledge of Portuguese language teachers. The preparation of the PLTSK will bring numerous benefits for education, such as better professional training, greater appreciation of the teaching profession and improvement in the quality of the discipline's teaching.